Malaysian rural community as consumer of health information and their use of ICT - Rohaya Mohd-Nor; Teddy Edwin Chapun; Constance Rinen Justin Wah (Universiti Kebangsaan Malaysian, 2013)
We investigate the use of ICTs in the context of the rural community of Sarawak, Malaysia and attempt to profile them as consumers of health information. A survey method was deployed to obtain data. The research outcomes reveal that a majority of our respondents reported that they do not actively seek online health information although they have an access to the Internet at home or workplace. A majority of them strongly agreed about the Internet's role in providing extensive and useful information about illnesses, and viewed enhancing ICT skills is quite important to search health information online effectively. They also strongly agreed that creativity is needed in designing online health information. However, there was a mixed view among the respondents about the Internet access reliability and coverage around their area. The findings of the research are useful for relevant agencies that aim to capitalize ICTs to disseminate vital health information to reach rural communities.